Diversity and Distribution of Shrimp Species (Decapods) in Babo Mangrove Forest Area, Bintuni Bay and Its Conservation Aspects - Andreas Luat; Rawati Panjaitan; Robi Binur (Pusat Publikasi Nusantara, 2024)
The study aims to identify the distribution and diversity of shrimp species (Decapoda) in the Babo, Bintun Mangrove Forest Area and its conservation aspects. This research has been carried out in the period from March 2024 to May 2024 in three villages in the waters of bintun Bay, Babo District, namely Nusei Village, Modan Village, and Amutu Village. The results of the analysis show that the number and abundance of shrimp at the three research stations in Babo are moderate. Only one species was found in the family Palaemonidae. The distribution of shrimp was influenced by the distribution of food. The average temperature of the shrimp was 25.06 °C, and the good temperature for the growth of white leg shrimp ranged from 22.0 - 29.6oC. The good temperature of shrimp ranges from 0 to 30oC. Among the six species, Penaeus indicus, jerbung, vannamei, and alpheus were the most abundant.